Letter from the President (Journal of EAHIL, 2017)
Dear Colleagues,As the trees in Edinburgh are beginning to turn gold and red, it’s pleasant think back to summertime and theconference in Rome! I hope you had a good summer, with holidays and excursions and plenty of fun.Since this issue is focussing on the conference in Rome, I thought it would be a useful exercise to draw on thefeedback that participants sent in, and look at the ideas for topics of future EAHIL events. So, having had a successfulconference in 2014, where do we want to go next?